Study on baseline characteristics and lipid profile abnormalities among type 2 diabetic patients attending urban diabetic care hospital, Bangladesh - Islam, Shajedul; Islam, Ariful; Bari, Wasim; Islam, Ariful; Islam, Sifat Ul; Islam, Mohammad Amirul (International Journal of Research in Medical Sciences, 2021)
Background: Altered levels of serum glycated hemoglobin (HbA1c) and lipid profile are prevalent in patients having type 2 diabetic mellitus (T2DM). Aim of the study was to investigate the relationship between serum HbA1c and lipid profile in T2DM to predict diabetic dyslipidemia. Methods: A structured questionnaire was filled up by each study subject to collect data according to study protocol including age, gender, BMI, BP, residential status, socio-economic status, educational status, physical activity, dietary habit, smoking and duration of diabetes. We collected blood samples from 270 type-2 diabetes mellitus (T2DM) patients aged 30-65 years after overnight fasting (10-12 hours). Then blood samples collected from T2DM patients were used to measure serum levels of HbA1c, fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) and high-density lipoprotein (HDL) were estimated by standard laboratory methods. Results: In this study, increased levels of fasting blood glucose (8.61 mmo/l), HbA1c (7.86%), TC (226.15 mg/dl), TG (193.34 mg/dl) and LDL (147.37 mg/dl), and decreased levels of HDL (40.36 mg/dl) were observed in T2DM patients. Moreover, the strong positive correlation of HbA1c levels with FBG, TC, TG, and LDL levels were found in this study. Besides, a very strong and significant negative correlation (R2=0.1822) between the serum levels of HbA1c and HDL were noted in this study. Conclusions: This study revealed a strong correlation between dyslipidemia and serum levels of HbA1c in T2DM patients.